Giant chondroid syringoma radiologically mimicking malignancy - Belkiz Uyar; Aynur Solak; Neslin Sahin; Hüsnü Bugdayci (Wolters Kluwer Medknow Publications, 2013)
Chondroid syringoma, or mixed tumor of skin, is a relatively rare, usually benign sweat gland tumor, most often seen in the head-and-neck region. Rare malignant examples have been reported, commonly involving the extremities. We report here a case radiologically mimicking a malignant neoplasm, but histologically-proven benign subcutaneous chondroid syringoma, arising in the anterior aspect of the upper thigh of a 59-year-old male.